ANALISIS YURIDIS STATUS HUKUM MANTAN NARAPIDANA DIKAITKAN DENGAN TEORI PEMIDANAAN DI INDONESIA - Leoni Capri Widyatama; Erdianto Erdianto; Syaifullah Yophie Ardiyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The life of ex-convicts is often viewed negatively. With this negative view, thephenomenon of injustice and discriminatory treatment by society arises for ex-convicts whohave a record as perpetrators of criminal acts. Such as ostracism, humiliation, limited rightsand the difficulty of ex-convicts in applying for jobs in companies. So that it is necessary toclarify the legal status of ex-convicts after being released from Correctional Institutions withthe aim of getting their rights back.The type of legal research is normative juridical with research on legal systematics,namely referring to certain laws and regulations or written law.With the data source in theform of secondary data consisting of primary, secondary and tertiary legal materials. Then,data collection techniques were carried out using legal material collection by means oflibrary research and then analyzing the data by conducting a qualitative descriptive analysis.The result of this reasearch is the juridical analysis of the legal status of ex -convicts,after serving a sentence according to the concept of criminal law is to return to being arespectable society as before and obtain full legal rights, but after the author analyzes whathappens is that the legal status of ex-convicts is not in accordance with justice and applicablelaw in Indonesia, due to various rules, discriminatory treatment and negativ e views fromsociety give injustice to ex-convicts which can be seen from the cases of ex-convicts who werediscriminated against in their own community and from the existing regulations limiting therights of ex-convicts especially when it come to getting a job. Effort that can be is that thegovernment must always prioritize human rights, such as by making legal products that areconsistent with and not contradictory to the 1945 Constitution of the Republic of Indonesia,especially Article 28 and the Human Rights Law.Keywords: Legal Status, Ex-convict, Criminal Theory